Linear Transformations of The Basis of The Motivating Word in Russian Inflection and Word Formation - Alimardanova Shahlo Ashurmamatovna (Zien Journals, 2022)
This article describes linear transformations of the stem of a motivating word, which include stem truncation and interfixation. The specificity of these phenomena of Russian word formation is considered from different points of view
Keywords: linear and nonlinear transformations; stem truncation; interfixation; morph